Rural Teacher Salary Impact Rural Students Drop Out in Developing Country - Yang Xingfang; Rizo Budi Prastowo; Minenhle Khumalo; Shabnam Musayeva (Universitas Riau, 2019)
Student dropout in rural area is one of the education problems that being faced by many countries. In this qualitative study, we used global and national documentation to explore and describe in-depth impact of rural teacher salary on rural student dropout in selected four developing countries, namely Azerbaijan, Colombia, Indonesia and South Africa. The data was obtained from the published data of each countries. The result shows that South African rural teachers get the highest salary of USD 2,524, followed by Colombia with USD 626,58, Azerbaijan USD 175 and Indonesia USD. 182.24. The Lowest percentage of rural student dropout in primary level is South Africa and Colombia (3% respectively), Junior High School level is Azerbaijan (8%) and for Senior High School is South Africa (27%). In conclusion it shows that rural teacher salary has negative impact on rural student dropout, but this impact will be more influential by support from many other factors. It is suggested that developing countries should increase rural teachers’ salary as the solution to decrease rural student dropout.